Moving toward Extensively Drug-Resistant: Four-Year Antimicrobial Resistance Trends of Acinetobacter baumannii from the Largest Department of Internal Medicine in Slovakia - Yashar Jalali; Adriána Liptáková; Monika Jalali; Juraj Payer (MDPI AG, 2023)
A. baumannii imposes a great burden on medical systems worldwide. Surveillance of trends of antibiotic resistance provides a great deal of information needed for antimicrobial stewardship programmes nationwide. Clinical data from long-term, continuous surveillance on trends of antibiotic resistance of A. baumannii in Slovakia is missing. One hundred and forty-nine samples of A. baumannii were isolated over a period of four years. A panel of 19 antibiotics from seven antibiotic categories were tested for the bacterium's susceptibility. Resistance results were evaluated, and the significance of patterns was estimated using simple linear regression analysis. All isolates were more than 85% resistant to at least 13 out of the 19 tested antibiotics. A significant rise in resistance was recorded for aminoglycosides and imipenem from 2019 to 2022. Colistin and ampicillin-sulbactam have been the only antibiotics maintaining more than 80% efficacy on the bacterium to date. A significant rise in extensively drug-resistant (XDR) strains among carbapenem-resistant (CR) isolates has been recorded. Multidrug-resistance (MDR) among all A. baumannii isolates and XDR among CR strains of the bacterium have risen significantly in the last four years.